Ballistic Efficiency of an Individual Epoxy Composite Reinforced with Sisal Fibers in Multilayered Armor - Lazaro Araujo Rohen; Frederico Muylaert Margem; Sergio Neves Monteiro; Carlos Maurício Fontes Vieira; Bruna Madeira de Araujo; Eduardo Sousa Lima (Materials Research, 2015)
Sisal fibers are among the natural lignocellulosic ones with great impact resistance for potential use in polymer composites. This work evaluates the ballistic efficiency of the distinct individual components of a multilayered armor. These include the front ceramic, the back metallic sheet and the intermediate layer as either the conventional aramid fabric or a novel sisal fiber reinforced epoxy composite. Sisal fibers incorporated in epoxy resin plates with volume fraction of 30% were ballistic tested using the 7.62 caliber ammunition. The fibers were embedded under pressure in the epoxy resin matrix and cured at room temperature for 24 hours. The tested specimens were examined by scanning electron microscopy.